2010
DOI: 10.1007/s00784-010-0427-5
|View full text |Cite
|
Sign up to set email alerts
|

Performance of laser fluorescence devices, visual and radiographic examination for the detection of occlusal caries in primary molars

Abstract: The aim of this in vitro study was to compare the performance of two laser fluorescence devices (LF, LFpen), conventional visual criteria (VE), ICDAS and radiographic examination on occlusal surfaces of primary teeth. Thirty-seven primary human molars were selected from a pool of extracted teeth, which were stored frozen at -20 °C until use. Teeth were assessed twice by two experienced examiners using laser fluorescence devices (LF and LFpen), conventional visual criteria, ICDAS and bitewing radiographs, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
64
4
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(85 citation statements)
references
References 33 publications
9
64
4
8
Order By: Relevance
“…[9][10][11] Besides, some studies have also shown a better performance of these devices than the radiographic examination, suggesting that they could be indicated as auxiliary methods for caries detection. 6,12,13 More recently, other fluorescence-based devices were introduced in the market and few data have been published concerning their performance. These devices are comprised of a light emitting diode (LED) and have been developed also aiming at caries detection.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Besides, some studies have also shown a better performance of these devices than the radiographic examination, suggesting that they could be indicated as auxiliary methods for caries detection. 6,12,13 More recently, other fluorescence-based devices were introduced in the market and few data have been published concerning their performance. These devices are comprised of a light emitting diode (LED) and have been developed also aiming at caries detection.…”
Section: Introductionmentioning
confidence: 99%
“…Aunque se ha observado una disminución en la prevalencia e incidencia de caries dental en la mayoría de los países industrializados, en los menos desarrollados todavía se observan importantes contrastes entre países y aún dentro de un mismo país (15). La presencia de caries dental depende de una serie de variables relacionadas con el huésped, el agente y el medio ambiente como en otras partes del mundo, donde se han asociado diversas variables con la caries dental.…”
unclassified
“…According to some of the results, the radiographic method was found to have worse performance than the visual examination and LF device methods when compared using sensitivity, specificity, accuracy, and AUC values (20)(21)(22)(23). This could be due to the depth of the caries lesion on the radiograph, difficulty in noticing hidden caries because of the fissure system and not removing all of the colorization on the occlusal region (21,24,25). Therefore, new methods are being researched for early caries lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The LF device had provided results than the radiographic method according to the assessment of sensitivity, specificity, accuracy, AUC, and likelihood ratio values. (12,21,22,27 or various other reasons. The radiographic method and the LF device supplied more diagnostic information than the visual method.…”
Section: Discussionmentioning
confidence: 99%